Baylor Faith and Character Study: Methods and Preliminary Findings. Issue 3 (29th April 2022) - Dougherty, Kevin D.; Glanzer, Perry L.; Robinson, Jessica A.; Ratchford, Juliette L.; Schnitker, Sarah A.
Abstract: For Christian colleges and universities, students' spiritual formation and character development are important outcomes. However, unlike academic outcomes of retention and graduation, systematic efforts to measure outcomes of faith and character are far from ubiquitous. The purpose of this article is to report the efforts of Baylor University to address the gap between mission and measurement. Guided by prevailing theories, an interdisciplinary research team launched the Baylor Faith and Character Study in August 2018. Data collection for the broader project involved surveys and interviews at three points in time: a student's first semester at Baylor, a student's final semester at Baylor, and 10 years after degree completion. Preliminary, cross-sectional findings from survey data reveal that levels of religious belief and practice were nearly equivalent for first-year students, seniors, and alumni, while seniors exhibited stronger character in several areas than first-year students. A discussion of conclusions and implications closes the article.